Karakteristik dewan direksi dan kinerja perusahaan - A An Arief Jusuf; Devina Widiana; Tessa Lonika Angelia (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2024)
The high demand for products from this sector supports the growth in the market capitalization value of companies in the energy sector. The managerial function of the board of directors can be observed through the company’s performance achievements. Based on the upper-echelon theory, perspectives influenced by the personal attributes of top management are used to evaluate situations and potential decisions. This study examines the influence of gender diversity, board size, and CEO tenure on company performance. The results of this study can serve as an additional reference for academics and practitioners. The population characteristics of this study include energy sector companies listed on the main board of the Indonesia Stock Exchange that published annual reports during the period 2012-2022. The data analysis method used is multiple linear regression with panel data, employing the pooled ordinary least squares (OLS) method. The Arellano robust standard errors in pooled panels were used for hypothesis testing interpretation. Gender diversity was found to have no significant effect on company performance. Board size has a positive effect on company performance, while CEO tenure does not significantly affect company performance.